Analisis Pengaruh Field of View (FOV) Terhadap Kualitas Citra Pesawat CT Scan di RSU Bali Jimbaran - Widya Karulina Imanda Muhamad; Gusti Ngurah Sutapa; I Gde Antha Asmawan; Rozi Irhas (Universitas Hamzanwadi, 2022)
It has been investigated the effect of field of view (FOV) on image quality produced by a CT Scan using the noise uniformity method with a phantom head. The FOV variations used are 180, 200, 220, 240 and 260 mm. The exposure time current and tube voltage used are 220 mAs and 130 kV, while the scan length and slice thickness used were 40 mm and 3 mm. Analysis of the effect of FOV variation on noise uniformity is determined by the standard deviation value obtained when performing ROI. Based on the standard deviation value, which shows that FOV variation affects the noise uniformity value, where the large increase in FOV, the noise uniformity is getting smaller and the resulting image quality is getting better